Phase Stability and Deformation Behavior of TiZrHfNbO High-Entropy Alloys - Wu, Yidong; Wang, Qinjia; Lin, Deye; Chen, Xiaohua; Wang, Tan; Wang, William Yi; Wang, Yandong; Hui, Xidong (Frontiers in Materials, 2020)
Strengthened by Oxygen doping, the single-phase body-center-cubic (BCC) TiZrHfNbO refractory high-entropy alloys (HEAs) become strong and ductile. However, phase stability at intermediate temperature and the effects of Oxygen addition on the deformation behavior during tensile tests need to be well understood. In the present work, the phase decomposition of (TiZrHfNb)100-xOx HEAs with Oxygen doping in the range of x=0, 0.5, 1, 1.5, 2 was examined at 873 K. The formation of hexagonal-close-packed (HCP) solid-solution precipitates in submicron size, enriched with Hf, Zr and O elements, were investigated by a combination of X-ray diffraction, transmission electron microscopy and atom probe tomography. Tensile tests of alloys annealed at both 1273 K and 873 K were conducted. It was found that doping Oxygen increased the yield strength and maintained ductility for alloys annealed at 1273 K, while formation of HCP precipitates after annealed at 873 K deteriorates the plasticity significantly. To unveil the deformation behaviors, in situ synchrotron X-ray diffraction experiments were applied in the current research. The single-crystal elastic constants and shear elastic anisotropy of HEAs with and without Oxygen doping were calculated and found similar to those of “Gum Metal” Ti alloy. Yet current HEAs possess higher BCC phase stability than “Gum Metal”, and no stress-induced phase transformation was detected during deformation.